2014
DOI: 10.1245/s10434-014-4097-4
|View full text |Cite
|
Sign up to set email alerts
|

High Neutrophil-to-lymphocyte Ratio Persistent During First-line Chemotherapy Predicts Poor Clinical Outcome in Patients with Advanced Urothelial Cancer

Abstract: An increased NLR persistent during first-line chemotherapy is an independent predictive factor for patients with advanced urothelial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 32 publications
1
89
0
Order By: Relevance
“…The prognostic role of the pretreatment NLR regarding RFS, PFS and disease-specific survival/cancer-specific survival (DSS/CSS) in bladder cancer patients was evaluated in 9, 7 and 9 studies, respectively. Of the 21 included studies, Hermanns’s study reported adjusted HRs and 95% CIs [29], while 3 studies reported HRs and 95% CIs derived only from a univariate analysis [42, 44, 45]; the remaining studies presented HRs and 95% CIs obtained by a multivariate analysis. With regard to the quality assessment of the included studies, the Newcastle-Ottawa Scale (NOS) scores ranged from 6 to 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic role of the pretreatment NLR regarding RFS, PFS and disease-specific survival/cancer-specific survival (DSS/CSS) in bladder cancer patients was evaluated in 9, 7 and 9 studies, respectively. Of the 21 included studies, Hermanns’s study reported adjusted HRs and 95% CIs [29], while 3 studies reported HRs and 95% CIs derived only from a univariate analysis [42, 44, 45]; the remaining studies presented HRs and 95% CIs obtained by a multivariate analysis. With regard to the quality assessment of the included studies, the Newcastle-Ottawa Scale (NOS) scores ranged from 6 to 8.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, nearly all the included studies reported multivariate HRs and 95% CIs. However, three studies involving mUC or uUC patients reported only univariate HRs and 95% CIs [42, 44, 45], which may have overestimated the prognostic role of the pretreatment NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that platelets induce circulating tumor cell epithelial-mesenchymal transition and promote extravasation to metastatic sites [25, 26]. Neutrophils promote adhesion and seeding of distant organ sites through the secretion of circulating growth factors such as VEGF and proteases [27, 28]. Lymphocytes play a crucial role in tumor defense by inducing cytotoxic cell death and inhibiting tumor cell proliferation and migration, thereby dictating the host's immune response to malignancy [29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lymphocytes, particularly cytotoxic T cells, play a crucial role in the antitumour immune response by promoting apoptosis and suppressing tumour growth 14 . Accordingly, the neutrophil-lymphocyte ratio (nlr), a cost-effective and simple inf lammatory parameter, might correlate bot h w it h pat ient outcome a nd w it h response to chemo therapy 15 . An elevated nlr has been described to correlate with poor outcome in a variety of cancers, including breast cancer [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%